Conceptualization and Development of Digital Leadership to Drive Corporate Digital Transformation for Sustainable Success - Phakamach, Phongsak; Panjarattanakorn , Darunee; Onsampant , Samrerng (International Journal of Educational Communications and Technology, 2023)
The digital age, marked by persistent demands for transformation, compels today’s workplaces to evolve into modern organizations powered by advanced digital technologies and innovation. This constant evolution exposes leaders to unique challenges birthed by escalating digitization. Consequently, Digital Leadership—defined by practical problem-solving skills—has become a prominent topic regarding the essential competencies managers must develop in this era. Digital Leadership is the discipline of steering an organization towards digital transformation to maintain competitiveness and agility in a swiftly changing landscape dominated by big data and social media. This discipline extends beyond managing businesses in the era of artificial intelligence or digital disruption; it also entails acquiring and applying appropriate digital skills to cultivate technological changes and innovation in diverse circumstances. This article explores the significance and benefits of proficient digital leadership in accomplishing business goals, delves into digital leadership’s concept, characteristics, and skills, and provides a comprehensive roadmap for developing digital leadership, fostering progressive digital leaders, and driving corporate digital transformation for sustained success. It demonstrates that comprehending and appropriately applying digital transformation is crucial for corporate leaders. The article also posits that digital leadership depends on specific factors such as organizational agility, engagement of skilled staff, leadership skill development, support from technology partners, investment, cultural adaptation, and the alignment of new digital technologies with existing ICT System. Lastly, the paper contends that building digital leadership skills necessitates comprehensive change management and strategic selection of digital talents or experts to propel the organization towards enduring success.